2017
DOI: 10.11648/j.jfa.20170505.13
|View full text |Cite
|
Sign up to set email alerts
|

Deadly Incidents in Bangladeshi Apparel Industry and Illustrating the Causes and Effects of These Incidents

Abstract: Abstract:The purposes of this paper are to explore the major deadly incidents of the apparel industry in Bangladesh and to illustrate the causes for these deadly incidents with the effect of these incidents. Different types of deadly incidents of the recent decade have made Bangladeshi apparel industry questionable. This paper will explore the causes of the different incidents and will show the precautionary measure of these problems of apparel industry which affected their sustainability and profitability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 3 publications
0
24
0
Order By: Relevance
“…The purpose of this study is to locate academic research focusing on the related studies of big data and finance. To accomplish this research, secondary data sources were used to collect related data [31,32,34]. To collect secondary data, the study used the electronic database Scopus, the web of science, and Google scholar [33].…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of this study is to locate academic research focusing on the related studies of big data and finance. To accomplish this research, secondary data sources were used to collect related data [31,32,34]. To collect secondary data, the study used the electronic database Scopus, the web of science, and Google scholar [33].…”
Section: Methodsmentioning
confidence: 99%
“…For example, CSR contributions were remarkable and then helped vulnerable people to survive in society after various natural disasters and human failures ensued around the world such as the 2004 Asian Tsunami (Chong, 2009;Fernando, 2010), the 2005 Hurricane Katrina in the United States (Johnson et al, 2011;M. Zhao et al, 2015), the 2006 Central Java Earthquake in Indonesia (Hendarto, 2009), the 2008 Hurricane Ike in the United States (Wang, 2009), the Weather Damaged Crop in 2008 in the United States (Johnson et al, 2011), the 2008 Sichuan Earthquake in China (M. Zhao et al, 2015), the 2010 Haitian Earthquake (Madsen & Rodgers, 2014), the 2011 Great Eastern Japan Earthquake and Tsunami (Kouadio et al, 2012), and the 2013 Rana Plaza Collapse in Bangladesh (Begum & Solaiman, 2016;Hasan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also determined various barriers to sustainable boiler operation, which are relevant in the context of the Bangladeshi apparel industry. For instance, Hasan et al [40] identified boiler explosions as a significant cause of industrial fire in apparel factories. A boiler explosion due to unsafe operation can cause fire and loss of life, hampering social and economic sustainability.…”
Section: Conceptualizing the Barriers To Sustainable Boiler Operationmentioning
confidence: 99%